Efisiensi Pengeluaran Pemerintah Daerah di Propinsi Jawa Tengah - Pertiwi, Lela Dina (Economic Journal of Emerging Markets, 2009)
Through the fiscal decentralization underlied the law No 22 in 1999, the local government now is more responsibility to develop its local economy. The goal of the fiscal decentralization is in order to increase efficiency of the local government in spending its budget. Under assumption that local government is much better know its own need than the central government, every spending will achieve a target according to society goals. This study is to measure the level of efficieny of local government spending in the case of education and health sector in all regency of the central Java province during 1999 and 2002 period by using the Data Envelopment Analysis. In 1999, the results show that the most efficiency on the education spending is Salatiga and it is Boyolali in 2002. Meanwhile, the most efficiency on the health spending is Salatiga and Surakarta achieves the highest efficiency on it in 2002 . Keywords: Efficiency, local government spending, DEA, education and health.